The Importance of Culture in Second and Foreign Language Learning - Ali, Sheeraz; Kazemian, Bahram; Mahar, Israr Hussain (Dinamika Ilmu: Jurnal Pendidikan, 2015)
English has been designated as a source of intercultural communication among the people from diverse linguistic and cultural backgrounds. A range of linguistic and cultural theories contribute meaningful insights on the development of competence in intercultural communication. The speculations suggest the use of communicative strategies focusing on the development of learners’ efficiency in communicating language through cultural context. However, the teaching of culture in communication has not been paid due importance in a number of academic and language settings of Pakistan and Iran. This assignment study indicates problems in view of teaching English as a medium of instruction in public sector colleges of interior Sindh, Pakistan and prescribed textbooks in Iranian schools. It also aims to identify drawbacks and shortcoming in prescribed textbooks for intermediate students at college level and schools. Therefore, the assignment study recommends integration of cultural awareness into a language teaching programme for an overall achievement of competence in intercultural communication.